Downregulation of miR‐375 in aldosterone‐producing adenomas promotes tumour cell growth via MTDH. (11th June 2015) - He, Juan; Cao, Yanan; Su, Tingwei; Jiang, Yiran; Jiang, Lei; Zhou, Weiwei; Zhang, Cui; Wang, Weiqing; Ning, Guang
Summary Objective Previous studies have investigated the genetic and molecular basis of primary aldosteronism (PA), a common cause of human hypertension, but the effects of microRNAs (miRNAs) on the adrenocortical cell proliferation and aldosterone production are largely obscure. Here, we characterized miRNA expression patterns in the subtypes of PA to gain a better understanding of its pathogenesis. Methods miRNA expression was assessed by microarray profiling analysis in aldosterone‐producing adenoma (APA), unilateral adrenal hyperplasia (UAH) and normal adrenal cortex tissues. Selected differentially expressed miRNAs were further validated in a validation cohort by qRT‐PCR. A gain‐of‐function approach was used to explore the functional role of the specific miRNA in vitro. Results Of 31 miRNAs including miR‐375, miR‐7 and miR‐29b were found to be significantly differentially expressed among these three groups. miR‐375 was the most downregulated one in adrenal cortex tissues from PA patients, and its expression level was inversely correlated with the tumour size in APA. Overexpression of miR‐375 in a human adrenocortical cell line (H295R) reduced cell proliferation and suppressed the expression of MTDH (metadherin, also known as astrocyte elevated gene‐1). Moreover, MTDH was verified as a direct target of miR‐375 through luciferase reporter assays. Knock‐down of MTDH in H295R cells attenuated Akt‐Ser473 phosphorylation and inhibited cell viability. Conclusion Our findings suggest that miR‐375 exerts its tumour‐suppressive function via targeting MTDH/Akt pathway and implicate a potential therapeutic target in PA.